The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1108/ijem-05-2022-0198
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the psychometric properties of the Cyberbullying Attitude Scale (CBAS) and its relation with teasing and gratitude in Indian collegiates

Abstract: PurposeThis study aims to examine the psychometric properties of the Cyberbullying Attitude Scale (CBAS) in Indian college students with the help of two independent studies.Design/methodology/approachThe first study investigated the factorial validity of the scale using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), resulting in a seven-item, two-component model of CBAS. Two statements were excluded owing to inadequate factor loading. The second study evaluated the reliability and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 63 publications
(100 reference statements)
0
11
0
Order By: Relevance
“…This broadened behaviour helps individuals develop social and psychological resources like self-resilience, optimism, hope and confidence . Social resources comprise trust, loyalty, respect and love for family, peers and others Bansal et al, 2022). On the other hand, psychological resources like hope and optimism may help the perpetrators and victims deal with shame and guilt arising out of weight-based teasing.…”
Section: Gratitude and Moderation Effect Of Gratitudementioning
confidence: 99%
See 4 more Smart Citations
“…This broadened behaviour helps individuals develop social and psychological resources like self-resilience, optimism, hope and confidence . Social resources comprise trust, loyalty, respect and love for family, peers and others Bansal et al, 2022). On the other hand, psychological resources like hope and optimism may help the perpetrators and victims deal with shame and guilt arising out of weight-based teasing.…”
Section: Gratitude and Moderation Effect Of Gratitudementioning
confidence: 99%
“…The incidences of weight-related teasing are both psychologically and physically wounding, especially when near and dear ones like parents are the perpetrators (Dahill et al, 2021). Victims can suffer from depression (Wright, 2018) and counterproductive work behaviour (Bansal et al, 2022). A study by Eisenberg et al (2003) suggested that the subjects (91.7%) whose parents or peers teased developed depressive symptoms in contrast to those who were not.…”
Section: Literature Review and Hypothesis Development Teasingmentioning
confidence: 99%
See 3 more Smart Citations